ANALISIS OPTIMALISASI INSTAGRAM @PEMPROV.SUMBAR SEBAGAI MEDIA INFORMASI PUBLIK DI RUANG PUBLIK - lestari, yayuk; Yenita, sandra Syarli; Sikumbang, Rinaldi (Universitas Islam Negeri Imam Bonjol Padang, 2024)
Social media platform Instagram has become a public communication channel used by governmental institutions to disseminate public information to the community. Nevertheless, Instagram @pemprov.sumbar lacks significant public interaction. This research aims to describe the optimization of the use of public space on Instagram @pemprov.sumbar. Furthermore, this study aims to describe the inhibiting factors of managing the Instagram account @pemprov.sumbar as a means of conveying public information. The theory employed in this study is the public sphere theory developed by Jurgen Habermas. This theory analyzes how the Instagram account @pemprov.sumbar functions as a public information medium within the public sphere. This research utilizes qualitative research methodology, a constructivist paradigm, with a descriptive approach. The research findings indicate that Instagram @pemprov.sumbar is not yet optimal in providing public information within the public sphere. The information provided is limited to ceremonial information. Moreover, the management process is influenced by inhibiting factors that prevent the creation of an optimal public sphere, one of which is laws related to public information openness that have not been adequately integrated into the realm of social media. Consequently, there is a lack of clear Standard Operating Procedures (SOPs) for managing public information media to deliver the required information to the public within the public sphere. The ambiguity of the SOPs for managing Instagram @pemprov.sumbar ultimately results in suboptimal public discourse.